"Assessment as Discourse": A Pre-Service Physics Teacher's Evolving Capacity to Support an Equitable Pedagogy - Edward G. Lyon (MDPI AG, 2013)
One way to view 'equitable pedagogy' is through an opportunity to learn (OTL) lens, meaning that regardless of race, class, or culture, a student has access to rigorous and meaningful content, as well as appropriate resources and instruction necessary to learn and demonstrate understanding of that content. Assessment holds a unique position in the classroom in that it can both uncover whether inequitable conditions exist (i.e., performance gaps, denied OTL) and provide an OTL by mediating communication between teacher and students regarding learning progress and what is important to learn. Nevertheless, individuals entering teacher education programs often hold deficit views toward marginalized students, such as Language Minorities (LMs), believe that assessment strictly serves to evaluate learning, and do not do consider how language and culture influence student thinking-views supplanting assessment's role at supporting an equitable pedagogy for LMs. Through surveys, interviews, program artifacts, and classroom observation, I report on a case study of one pre-service physics teacher, Dean, to depict how his expertise at assessing science did evolve throughout his yearlong teacher education program in terms of (a) becoming more knowledgeable of the role of language and (b) developing a belief in incorporating 'discourse' while assessing science. Within the case study, I analyze one particular episode from Dean's teaching practicum to highlight remaining challenges for pre-service teachers to integrate science and language in classroom assessment-namely, interpreting students' use of language along with their understanding of core science ideas. The findings underscore the need for connecting language and equity issues to content-area assessment in teacher preparation.